Roles and mechanism of IL-11 in vascular diseases - Wu, Jiacheng; Ma, Wenrui; Qiu, Zhihua; Zhou, Zihua (Frontiers in Cardiovascular Medicine, 2023)
Vascular diseases are the leading cause of morbidity and mortality worldwide. Therefore, effective treatment strategies that can reduce the risk of vascular diseases are urgently needed. The relationship between Interleukin-11 (IL-11) and development of vascular diseases has gained increasing attention. IL-11, a target for therapeutic research, was initially thought to participate in stimulating platelet production. Additional research concluded that IL-11 is effective in treating several vascular diseases. However, the function and mechanism of IL-11 in these diseases remain unknown. This review summarizes IL-11 expression, function, and signal transduction mechanism. This study also focuses on the role of IL-11 in coronary artery disease, hypertension, pulmonary hypertension, cerebrovascular disease, aortic disease, and other vascular diseases and its potential as a therapeutic target. Consequently, this study provides new insight into the clinical diagnosis and treatment of vascular diseases.